Gastric calcifying fibrous tumor suspected to be complicated with immunoglobulin G4-related disease treated by laparoscopy and endoscopy cooperative surgery: a case report - Ryoga Hamura; Tomoki Koyama; Masahiko Kawamura; Takeshi Kawamura; Mayo Nakamura; Katsuhiko Yanaga (Surgical Case Reports, 2019)
Abstract Background Calcifying fibrous tumor (CFT) is a rare benign soft tissue lesion. Case presentation A 30-year-old woman was admitted to our hospital with complaints of epigastralgia. A 15-mm submucosal tumor was identified in the greater curvature of the superior body of the stomach by upper gastrointestinal endoscopy. Endoscopic ultrasonography revealed a hypoechoic lesion with an acoustic shadow consistent with calcification. Computed tomography showed a gastric tumor with calcification. A gastrointestinal stromal tumor was diagnosed, and gastric wedge resection was performed by laparoscopy and endoscopy cooperative surgery. On pathological examination, the tumor was identified to be a CFT. Postoperative serum IgG4 levels were 26.0 mg/dl, which supported the diagnosis of probable immunoglobulin G (IgG) 4-related disease, according to the comprehensive diagnostic criteria of IgG4-related disease. The patient was discharged on postoperative day 7 and remains well with no evidence of tumor recurrence for 2 years after resection. Conclusion We herein reported a patient with a gastric CFT suspected to be complicated with immunoglobulin G4-related disease that was successfully treated by laparoscopy and endoscopy cooperative surgery.